Tłumaczenia bułgarskie literatury polskiej w 2014 roku - Dimitrova, Marinella (Przekłady Literatur Słowiańskich, 2015)
Bulgarian translations of Polish literature in 2014 The article focuses on the Polish literary works translated into Bulgarian in 2014. We will point to the most important trends defining the main characteristics of Bulgarian translations of Polish writers and the possible reasons why they have been chosen. Next, the titles of the translated works that were warmly received by the Bulgarian audience will be presented. We will also pay attention to the most active modern translators and the brightest representatives of the new translators’ generation in Bulgarian literature. Key words: Polish literature, translation, contemporary, trend, influence, Bulgarian literature